Research on Droplets Deposition Characteristics of Anti-Drift Spray Device with Multi-Airflow Synergy Based on CFD Simulation - Guiju Fan; Siyu Wang; Peng Bai; Dongwei Wang; Wenjie Shi; Chengqiang Niu (Applied Sciences, 2022)
With the increase in orchard areas and the transfer of rural labor, various air-assisted sprayers have been widely used in China. However, the problem of off-target drift still exists, which has caused pesticide waste and environmental pollution. In order to improve the droplet deposition in the canopy of fruit trees, a V-shaped anti-drift spray device with multi-airflow synergy was designed in this paper. A droplet spatial motion model was constructed, and the anti-drift mechanism of multi-airflow synergy was clarified based on particle dynamics analysis. The influences of spray pressure and V-shaped wind speed on droplet movement were investigated by Matlab, and the experimental results showed that the machine’s anti-drift effect was better when the V-shaped wind speed ranged from 15 m/s to 25 m/s. According to modern orchards with low root stock in a high-density planting, a simulation model of the flow field between the spray device and the fruit trees canopy was established by the method of computational fluid mechanics (CFD). By considering crosswind speed, V-shaped wind speed, and spray pressure, three-level simulation experiments of droplet deposition were designed for each factor using a partial multivariate orthogonal regression method. The influence of V-shaped wind speed on the droplets’ spatial distribution was analyzed, and the prediction model of the drift distance of the droplets’ deposition center was established. The simulation results showed that the three factors had a significant influence on the droplets’ deposition characteristics, and the degree from big to small was V-shaped wind speed, crosswind speed, and spray pressure. The fitting degree of the prediction model was high, and the correlation coefficient was 0.998. The anti-drift experiments of the machine were carried out, and the results showed that when the crosswind speed, the spray pressure, and V-shaped wind speed were 2.2 m/s, 0.52 MPa, and 20.8 m/s, respectively, the droplet drift rate was 29.2% lower than that of single-airflow. The drift distance of the droplets deposition center was 5.0 cm, which was consistent with the prediction model. The research can provide a basis for the design and parameters optimization of the similar sprayers used in modern orchards with low root stock in a high-density planting.